2009
DOI: 10.2147/ijwr.s4567
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dominant lactic acid bacteria isolated from grape juices. Assessment of its biochemical activities relevant to flavor development in wine

Abstract: We investigated the dominant lactic acid bacteria (LAB) from grape juice and commencement of malolactic fermentation (MLF) samples of a cellar located in Argentina and assessment of its β-glucosidase activity and butter aroma compounds production. LAB number found in grape juice (approximately log 10 3.3) was lower than that obtained in the MLF samples. Oenococcus oeni was predominant, accounting for 68% of the 81 LAB isolated. Majority of whole cells derived from O. oeni cultures at the end of the exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Higher numbers of LAB obtained from white varieties compared to red ones were also reported by Bae et al (2006), which has been attributed to the fact that some phenolic compounds only present in red varieties can produce a toxic effect on bacteria (Reguant et al, 2000). The fluctuating populations of LAB observed in wine at different stages of MLF coincides with Saguir et al (2009) and González-Arenzana et al (2012), who reported that lower counts of LAB at the beginning of MLF increased throughout the process, reaching up to 8 Log CFU⋅ml -1 .…”
Section: Discussionsupporting
confidence: 80%
“…Higher numbers of LAB obtained from white varieties compared to red ones were also reported by Bae et al (2006), which has been attributed to the fact that some phenolic compounds only present in red varieties can produce a toxic effect on bacteria (Reguant et al, 2000). The fluctuating populations of LAB observed in wine at different stages of MLF coincides with Saguir et al (2009) and González-Arenzana et al (2012), who reported that lower counts of LAB at the beginning of MLF increased throughout the process, reaching up to 8 Log CFU⋅ml -1 .…”
Section: Discussionsupporting
confidence: 80%